Production potential of sago forests in different habitat types in Sentani watershed, Papua, Indonesia - PETRUS A. DIMARA; RIS HADI PURWANTO; AMILDA AURI; RUSDI ANGRIANTO; WOLFRAM Y. MOFU (Society for Indonesian Biodiversity, 2023)
Abstract. Dimara PA, Purwanto RH, Auri A, Angrianto R, Mofu WY. 2023. Production potential of sago forests in different habitat types in Sentani watershed, Papua, Indonesia. Biodiversitas 24: 3924-3931. Sago possesses a substantial carbohydrate content, rendering it a promising alternative for ensuring food security. This study aimed to assess the potential for sago production in Sentani watershed, Papua Province, Indonesia across diverse growing environments, namely dryland, temporarily flooded, and prolonged flooded habitats. This research combined spatial analysis and field-based study. Spatial analysis utilized Landsat 8 satellite imagery from the year of 2021 analyzed using supervised classification and overlay methods to differentiate sago habitat types. Field study used the combination of line transect and systematic circular plot methods to assess the structure and composition of sago vegetation. Field study also determined starch yield of sago plant by felling the plant and extracting the starch. The results showed that there are 13 local sago varieties according to the Sentani language, namely ebhesum, folo, hobholo, manno, phane, phara, rondo, ruruna, osukhulu, wani, yakhalobe, yakhe, and yebha. Sago plants growing on dryland, temporarily flooded, and prolonged flooded habitats covered an area of 1,246.35 ha (15.89%), 4,820.49 ha (61.46%), and 1,775.92 ha (22.64%), respectively. The plant grew in clumps with 10, 13, and 8 varieties in the dryland, temporarily flooded, and prolonged flooded habitats, respectively. The total starch production reached 13,999.57 tons.year-1with production in dryland, temporarily, and prolonged flooded habitats amounting to 2,132.88 tons.year-1, 1,031.39 tons.year-1, and 1,335.31 tons.year-1, respectively. Meanwhile, the areas with the highest starch production were West Sentani, Sentani, and Waibu Sub-districts for the dry, temporary, and flooded habitats. Our findings suggest that two sago varieties, namely pharaand yebha, are recommended for cultivation because they are more adaptive and have high starch yield compared to other sago varieties.